The biological function of the long non-coding RNA endogenous born avirus-like nucleoprotein in lung adenocarcinoma is mediated through the microRNA-655-3p/B-cell lymphoma-2 axis. Issue 4 (1st April 2022) - Wang, Xiaopeng; Yin, Jing
ABSTRACT: Lung adenocarcinoma (LUAD) is a subtype of lung cancer, and therapy remains a great challenge. A growing body of evidence shows that long-chain non-coding RNAs (lncRNAs) play an important role in the occurrence and development of LUAD. This study investigated the roles and mechanisms of action of EBLN3P in LUAD. The bioinformatics software starBase and TargetScan were used to predict the binding sites of the lncRNA endogenous born avirus-like nucleoprotein (EBLN3P) and microRNA (miR)-655-3p in LUAD. The regulatory role of EBLN3P and miR-655-3p in cell proliferation was verified through the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2 H-tetrazolium bromide (MTT) assay. The binding sites between EBLN3P, miR-655-3p, and B-cell lymphoma-2 (Bcl-2) were assessed using dual-luciferase reporter assay, western blotting, and quantitative reverse transcription polymerase chain reaction (qRT-PCR). Flow cytometry (FCM) was performed to analyze the apoptotic rates of A549 cells after transfection. The results revealed that EBLN3P was upregulated, whereas miR-655-3p was downregulated in LUAD cell lines (A549 and NCI-H23). Bioinformatics analysis and dual-luciferase reporter assays indicated that EBLN3P interacted with miR-655-3p. Knockdown of EBLN3P notably inhibited the bioactivity and induced apoptosis in A549 cells by upregulating miR-655-3p. Mechanistically, miR-655-3p inhibits cell viability and induces apoptosis by inhibiting Bcl-2 expression. The high expression of Bcl-2 reversed the impact of miR-655-3p on the inhibition of cell bioactivity and induction of apoptosis in A549 cells. In conclusion, this study demonstrated that EBLN3P silencing inhibits bioactivity and induces apoptosis via the miR-655-3p/Bcl-2 axis, providing a potential therapeutic target for lung adenocarcinoma. Graphical abstract: uf0001